ANALISIS PERCAKAPAN NETIZEN PADA INSTAGRAM GANJAR PRANOWO MENJELANG KONTESTASI POLITIK 2024 - Ahmad Toni (IAHN Gde Pudja Mataram, 2022)
This study is about the conversations of netizens on Ganjar Pranowo’s Instagram account ahead of the 2024 political contestation with conversational elections in September dan Oktober 2022. The method used in this study is conversational analysis with primary data taken from the netizen conversation system on Ganjar Pranowo’s Instagram account and secondary data from vorius other literatures. The results showed that the conversation system was focused on word choice or netizen’s diction on word RI-1 is the Republic of Indonesia One which means the number one person in the Republic of Indonesia, the diction ‘Capres’ or the abbreviation of Canditate Presiden provides an explanation of the political situation and conditions by 2024. In the conversational system the use of idioms includes: ‘Let’s go’ is defined as support for Ganjar Pranowo’s political carrer and leadership in the 2024 election, ‘political smell’ is defined as the 2024 political situation and condition, ‘Ganjar cravings’ are defined as the proximity and ease of people meeting Ganjar Pranowo in any situasion and condition. In the conversation about thesociological meaning of Javanese cultural values associated with Joko Widodo’s Leadership relay.